A teologia de Puebla: lutas, ambiguidades e continuidades - Passos, João Décio (Horizonte, 2019)
The reflection on the theology of Puebla exposes two theological tendencies present in the assembly and in the final document. The first tendency of a classical matrix rests on an essentialist view of reality. The second is structured from the historicity and has its final elaboration in the category signs of the times, consecrated by the Council. The theological batlle results in the conclusive text of Puebla and expresses the batlle for the meaning of Vatican II. Nevertheless, this hermeneutic batlle, the reception of the Third Conference will take place in a historical and liberating perspective in continuity with the consolidated tradition of the Medellin Conference. The current historical context is a presupposition that reaffirms the current relevance of the teachings of Puebla. The reflection starts from the historical possibilities of Puebla's realization, verifies the internal struggle for the meanings of Vatican II and Medellín that occurred within the process and concludes with the presentation of the Conference receptions.